Participant experiences of a post-release electronic monitoring program for domestic violence in New South Wales, Australia - Hwang, Ye In J. (Journal of criminology, 2021)
Electronic monitoring has been increasingly used internationally with recent implementation in Australia for those convicted of domestic violence offenses. It is timely and important to gain a better understanding of the physical, psychological, social, and offending-related experiences and impacts of electronic monitoring on this group to inform further implementation. This study describes the experiences of individuals who were subject to a post-release electronic monitoring program for domestic violence in the state of New South Wales, Australia. Semi-structured phone interviews were conducted with 16 men who had recently experienced electronic monitoring. Thematic analysis was used to investigate common themes across participants? experiences. Demographic and basic quantitative health data were also collected. Five themes were identified: (a) confusion regarding program practices, (b) awareness and pressure of monitoring, (c) social exclusion effects, (d) felt and enacted stigmatization, and (e) ?for them not for me.? The findings reveal participants were highly aware of their being monitored, with a mix of positive and negative responses to this cognizance. Being electronically monitored had several flow-on effects on participants? lives, creating challenges in social spheres across work and personal life. Stigma, both felt and enacted, featured heavily in participants? responses. Individual factors that may affect program adherence were also identified, including education level and intent to commit a crime. Further quantitative work will be useful for informing a more complete understanding of the relationship between program experiences and outcomes such as reoffending and post-release community integration.